Pengaruh Perilaku Keuangan, Gaya Hidup, Financial Attitude dan Literasi Keuangan Terhadap Perilaku Konsumtif Mahasiswa Fakultas Ekonomi dan Bisnis Universitas YPPI Rembang - Edo Yondha Wibowo; Riskin Hidayat (Otonomi, 2023)
Thie purpose of this study was to prvove the effect of financial behavior, lifestyle, financial attitude and financial literacy on the consumptive behavior of students of the Faculty of Economics and Business, University of YPPI Rembang. Data collection techniques in research conducted using a questionnaire method. Meanwhile, the sample selection used a purposive sampling method so that the sample in this study was 100 students. The data analysis technique used is multiple linear analysis techniques with SPSS 25 tools. The results of the determination test show that the independent variables used in this study affect the dependent variable by 38.3%, while the remaining 61.7% is explained by other variables in outside the research model. From the test results, it can be concluded that financial behavior variables have a non-significant negative effect on consumptive behavior, while lifestyle variables have a significant positive effect and variables on consumptive behavior, as well as financial attitude and financial literacy variables have a non-significant positive effect on consumptive behavior of students at the University of the Faculty of Economics and Business YPPI Rembang.